Impact of water origin and composition on the desalting of fully salt-cured cod - Dargentolle, Cecile; Dupont, Maxime; Sveinsdóttir, Hildur Inga; Arason, Sigurjón; Sveinsdóttir, Kolbrún (Zenodo, 2024)
Salt-cured cod is a product popular in Mediterranean countries like Portugal and Spain. Usually, consumers desalt the product in their kitchen, or it is desalted by the producers in the factory. However, a large portion of those products is produced in Iceland and sold fully salt-cured to buyers in the Mediterranean countries. In recent years, market requirements have changed towards more demand for desalted products. Huge amount of water is needed for desalting, and water in Iceland is generally cheaper than in Mediterranean countries. In order to examine if desalting is a viable option for the producers of fully salt-cured cod in Iceland, composition and effect of water used for desalting in Iceland, Spain and Portugal on end-product quality was compared. Brine injected products were desalted with water from three locations in Iceland and one in Spain. Pickle salted products were desalted with water from two locations in Iceland and one in Portugal. Mineral composition and pH of water from the different locations was measured. During desalting, pH, temperature, salinity and weight were measured, and after desalting, cooking yield, colour, texture, water content and salt content of samples was measured. The different mineral composition and pH of the water obtained from the different locations affected the desalting process and the properties of the resulting desalted products. Further, the effects depended on the salt-curing method. When the brine salted samples were studied, the water for desalting containing a medium amount of minerals and a low pH (close to 7) gave the best results in terms of texture and water uptake as well as cooking yield. When the mineral content of the desalting water was high, the texture was negatively affected. For the pickle salted samples, high levels of sodium and potassium associated with the lowest levels of calcium and medium levels of magnesium, provided the best results, if the mineral content was low, the texture properties were negatively affected. _____ Saltfiskur er ...